2016
DOI: 10.1111/petr.12792
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and markers of erythropoiesis in pediatric kidney transplant recipients compared to children with chronic renal failure

Abstract: PTA and anemia of CKD share a similar pathogenesis. However, PTA may be disproportionate to the reduction in the GFR. Data relating to the mechanism of PTA are scarce. We evaluated the erythropoiesis parameters in pediatric kidney recipients compared to children with CKD. A total of 100 patients (54 post-kidney TX, 46 with CKD) were enrolled in the single-center cohort study. GFR was found to be significantly lower in the CKD group (49.7±22.4 vs 72.9±28.5 mL/min/1.73 m², P<.001); anemia was significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In our cohort of pediatric kidney transplant recipients, we evaluated associations among hemoglobin concentrations, erythropoietic factors, iron-related factors, and FGF23. There was a high prevalence of anemia, consistent with what has been observed in other pediatric kidney transplant studies [1][2][3][4][5][6]. Interestingly, the parameter most strongly associated with hemoglobin SDS was total FGF23 concentrations, which were inversely associated with hemoglobin SDS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our cohort of pediatric kidney transplant recipients, we evaluated associations among hemoglobin concentrations, erythropoietic factors, iron-related factors, and FGF23. There was a high prevalence of anemia, consistent with what has been observed in other pediatric kidney transplant studies [1][2][3][4][5][6]. Interestingly, the parameter most strongly associated with hemoglobin SDS was total FGF23 concentrations, which were inversely associated with hemoglobin SDS.…”
Section: Discussionsupporting
confidence: 87%
“…In pediatric kidney transplant recipients, anemia is common [1][2][3][4][5][6] and associated with worse allograft function [5,6]. The etiology of post-transplant anemia is oftentimes complex and multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to expectations, patients within the RTx group without iron deficiency exhibited higher hepcidin levels compared to those with functional iron deficiency. We could not conclude that higher hepcidin and ferritin levels indicate inaccessible iron overload, rather we may postulate that RTx recipients may have better iron storage similar to findings of former studies 35 …”
Section: Discussionmentioning
confidence: 56%
“…34 36,37 It has been indicated that several factors, including chronic inflammation, the myelosuppressive effect of medications such as immunosuppressive agents, ACEI, and antibiotics, may influence the responsiveness to EPO. 35,38 We could not find any correlations between EPO/Hb ratios and inflammation markers, medications, CsA has been shown to inhibit EPO release in vitro, while hematological toxicity has rarely been attributed to TAC. 42 The report…”
Section: Ta B L Ementioning
confidence: 70%
“…Due to a high turnover rate of iron during chronic dialysis and because of peri‐surgical blood loss, ID is the major cause of early‐onset anemia 7,12‐14 . On the other hand, late‐onset anemia (>12 month post‐transplant) is principally driven by inadequate nutrition and EPO deficiency that results from impaired allograft function 3,15,16 …”
Section: Introductionmentioning
confidence: 99%